Evaluasi Kualitas Website Perpustakaan Universitas Muslim Nusantara Alwashliyah Menggunakan Metode Webqual 4.0 - Ineke Mayliningrum Nst; Neila Susanti; Franindya Purwaningtyas (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This thesis discusses the Quality Evaluation of the UMN Al Washliyah library website using the webqual 4.0 method, where this research aims to ensure that library users use the website as a tool to search for information needs so that users no longer come directly to the library. This research uses a quantitative method with a comparative causal approach with sampling using the Accidental Sampling technique. The results from the research data that I obtained X1 has an average of 11.8 and has a percentage of 80%, the results are good, The percentage is 107% because users already understand and have good judgment, Y has an average value of 20.47 with a percentage value of 96%. So that the overall results show positive results received by the users of the UMN Al Washliyah library. The conclusion of the results of this research is quoted from the results of the coefficient of determination showing that the UMN Al Washliyah library website as an independent variable or variable that influences the quality of the UMN Al Washliyah library website is 78 % and the remaining 22% is caused by factors that are not related to the variables studied or other variables.